Coined in “Imaginative Molds”: Ahab’s Ecuadorian Doubloon and the Power of the Middle of the World in Moby Dick - Ramírez Paredes, Roberto Marcos (2025)
In Moby-Dick by Herman Melville, Captain Ahab promises a gold doubloon to the first sailor who spots the white whale. The coin, which is from Ecuador, functions as a miraculous object that triggers passions and interpretations. Why does this particular doubloon hold such power? To answer this question, the present essay explores the history of the doubloon and the representations of the equatorial and the Ecuadorian in the novel. It also delves into the mythical thinking surrounding the “middle of the world” and includes an analysis of Melville’s short story “The Veranda”.